Teacher training for the practice of interculturality in higher education - Herrera Siles, Sorayda del Carmen (Revista Universitaria del Caribe, 2019)
Indigenous and Afro-descendant peoples have historically been subjected to discrimination, marginalization, inequality, injustice, exclusion, institutionalized racism, poverty and social violence, from there, the struggles and realities of Latin America are diverse according to the spaces and conditions of each of the countries and villages. From the Universal Declaration of Human Rights until today there are advances in the legal framework in the international and national sphere in the recognition of the plurality and cultural diversity in the Political Constitution of each country, the approval of norms and laws specific to the Peoples' rights with emphasis on legal, health and education; however, effective application is still a utopia, some are made from the discourse, without really sharing power in the different decision-making spaces, as well as the equitable redistribution of resources or promoting equal opportunities that hinder violation of human rights. This essay gives an overview of teaching in its basic functions of training men and women, the articulation of endogenous knowledge with the exogenous, research and community social extension. Finally, as a conclusion, challenges and / or pending actions are presented to ensure the intercultural university model.